2012
DOI: 10.1097/nnr.0b013e31823bc451
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving of Older Chinese People With Dementia

Abstract: The model findings lend support that caregivers' cognitive appraisal and coping explain some observed individual differences in stress response and outcomes. The findings broaden understanding of the effects of familism on caregivers' psychological health. In the future, programs should include interventions for caregivers, as well as interventions for care recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
4
27
0
2
Order By: Relevance
“…This interpretation extends previous studies, which have shown indirect effects of caregiving characteristics on HRQoL through strain [29,28], but have not reported mediation [30,27]. Specifically, chains-of-risk refers to the accumulation of risk factors over time, which tend to lead to one another [32].…”
Section: Discussionsupporting
confidence: 83%
“…This interpretation extends previous studies, which have shown indirect effects of caregiving characteristics on HRQoL through strain [29,28], but have not reported mediation [30,27]. Specifically, chains-of-risk refers to the accumulation of risk factors over time, which tend to lead to one another [32].…”
Section: Discussionsupporting
confidence: 83%
“…Concerning objective 2, to characterize the burden‐satisfaction profile groups, we found that the coexistence of high satisfaction and high perceived burden was accompanied by caring for relatives with high care requirements, supporting the hypothesis that satisfaction with care can be experienced despite the presence of stressful caregiving conditions (Liu et al, ). The low satisfaction‐low burden profile was characterized by a higher proportion of male caregivers and caregivers who were not spouses or offspring (greater kinship distance), and by caring for relatives with low care requirements, suggesting that this profile may be associated with a low level of involvement in care.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies on satisfaction with care (e.g., Liu, Insel, Reed, & Crist, ) have been based on Bradburn's two‐factor theory of emotional wellbeing (1969), and on subsequent developments of this theory by Lawton et al () in the field of dependent elderly relative care.…”
Section: Coexistence Of Satisfaction and Burdenmentioning
confidence: 99%
“…In addition, older caregivers may become experienced and resilient in response to demands of care over time, which, in turn, generates a greater sense of inner strength and experienced greater satisfaction. In accordance with the values of familism, family members emphasizing identification, allegiance, reciprocity, and attachment to their families may view caring for their loved ones as a normative family event, having a deeprooted desire to commit caregiving activities, and even gaining satisfaction from caregiving (Liu, Insel, Reed & Crist, 2012). The perception of losing face associated with stigma attached to mental illness may lead families to rely on the immediate or significant relatives and friends (Chien et al, 2007).…”
Section: Discussionmentioning
confidence: 99%